Fumigant toxicity of lemon grass essential oil against rice weevil Sitophilus Oryzae L. (Coleoptera:Curculionidae) / Muhammad Sham Solahuddin Haq Azhar - Azhar, Muhammad Sham Solahuddin Haq (Faculty of Plantation and Agrotechnology, 2019)
The usage of chemical insecticides in Malaysia under post harvests storage to control pest can produce harmful effects to human and environmental whether directly or indirectly manners. The over usage of chemical treatment can cause of gradual pest resistances to chemical over the time. This resistance problems also can cause higher input usage such as cost for pest management. The main objective of this research is to investigate the effectiveness of essential oil in controlling rice the weevil. The location of this study was carried at UiTM entomology laboratory. The rice weevil or knows as Sitophilus oryzae is used as a test insect in this experiment. There were 10 different level of essential oil concentration as treatment and the essential oil used are citronella extract. This experiment using fumigant effect towards test insects exposed for 7½ hours .After the data collected and analyzed, the findings from this experiment showed the LC50 of 50% concentration level is 19.768ml/0.5ml and the LC99 of 90% concentration level at 83.999 ml/0.5mL which is the recommended level for rice weevil to reach its mortality level. The p-Value obtained is 0.00 less than 0.05 that showed there was significant different between amount essential oil used in fumigation control and the mortality of weevil .The times taken to reach mortality level were more concise than other concentration level. Thus, essential oil can be used to control the rice weevil.